Penerapan Sistem Pembayaran Digital dalam Berdagang - Nisrina, Ulfah Laila (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study aims to explore the implementation of digital payment systems in trading activities using a qualitative descriptive approach. The research focuses on understanding traders’ experiences, perceptions, and adaptation processes in adopting digital payment methods within their daily business operations. Data were collected through in-depth interviews and direct observation of traders who have implemented, or are in the process of implementing, digital payment systems. Informants were selected purposively to capture diverse backgrounds, types of businesses, and levels of technology adoption. The data were analyzed using thematic analysis to identify patterns, meanings, and relationships among the findings. The results show that digital payment systems are generally perceived by traders as facilitating faster and more convenient transactions, increasing customer satisfaction, and supporting business competitiveness. However, the study also reveals several challenges, including limited digital literacy, concerns about transaction security, and dependence on internet connectivity. The discussion indicates that successful implementation of digital payment systems is not solely determined by technological availability but is strongly influenced by traders’ perceptions, adaptability, and environmental support. This study concludes that digital payment systems have positive potential for small-scale trading activities, provided that adequate education, assistance, and infrastructure support are continuously strengthened.